Plan estratégico para la junta administradora de agua potable del sistema regional Chipe Hamburgo, cantón La Maná, periodo 2015-2019 - Suárez Pisco, Andrea Liseth (2016)
A compulsory need is currently to rely on good service of drinking water for the inhabitants of the enclosure Chipe Hamburgo and surrounding enclosures, due to that this assistance is guaranteed in the Constitution, however in some small towns flaws arise due to lack of appropriate decisions decision allowing this elementary service for the population. In the case of the enclosure Chipe Hamburgo and surrounding areas drinking water does not meet the expectations of the population, due to the lack of coverage for the entire population, which can cause problems on the health of the inhabitants. The present research project presents a detail about the implementation of a "Strategic Plan for Junta Administradora de Agua Potable del Sistema Regional Chipe Hamburgo, Canton La Mana, period 2015-2019" from an analysis of the current problematic situation of the company, is formulated the problem and defined the objectives, then discusses the conceptual and reference framework structured by relevant information found in books related to the research. The analysis on the current situation of the company could be concluded that there is a negative scenario in the technical and administrative levels that endanger their stability; also in the company are missing strategies to achieve objectives that allow prioritize problems and propose solutions. The Junta Administradora de Agua Potable del Sistema Regional Chipe Hamburgo, is not fulfilling the goals established by its directors in the absence of a strategic planning that will become a solid purpose to gain sustainable advantage in time. In the established plan to follow strategies are of great importance for decision-making on administrative levels, technical and financial of the key emprise.